The Litchfield Pluton in South-Central Maine: Carboniferous Alkalic Magmatism in northern New England, USA - West, David P; Bradley, Dwight; Coish, Raymond (Atlantic Geoscience, 2016)
The Litchfield pluton is a poorly exposed 7 km2 composite alkalic intrusive complex that cuts previously deformed and metamorphosed Silurian turbidites in south-central Maine. The pluton includes a variety of alkaline syenites, including the type locality of “litchfieldite”, a coarse-grained cancrinite, sodalite, and lepidomelane bearing nepheline syenite first recognized over 150 years ago and common in many petrologic collections. A new U-Pb zircon age of 321 ± 2 Ma from the nepheline syenite is interpreted to represent the crystallization age of the plutonic complex. A new biotite 40Ar/39Ar age of 239 ± 1 Ma from the syenite is similar to previously published mica ages from the surrounding country rocks and dates the time of regional cooling in the area below 300°C. Whole rock geochemical analyses from rocks of the Litchfield pluton are compatible with strongly alkaline A-type granitoid rocks that formed in a within plate or continental rift tectonic setting. The age and geochemical characteristics of the alkalic igneous rocks near Litchfield are consistent with a model that invokes the generation of a small volume of alkalic magma beneath south-central Maine during a period of Carboniferous transcurrent tectonism in the northern Appalachian orogen.